On‐Surface Metalation and 2D Self‐Assembly of Pyrphyrin Molecules Into Metal‐Coordinated Networks on Cu(111). Issue 1 (12th December 2016) - Li, Jingyi; Wäckerlin, Christian; Schnidrig, Stephan; Joliat, Evelyne; Alberto, Roger; Ernst, Karl‐Heinz
Abstract : The metalation of the tetradentate molecule pyrphyrin by copper substrate atoms on a Cu(111) surface is studied. Pyrphyrin, in contrast to porphyrin, consists of four fused pyridine groups instead of pyrrol groups. Using thermal desorption spectroscopy (TDS) and N 1s X‐ray photoelectron spectroscopy (XPS), we show that metalation of the monolayer of pyrphyrin with Cu atoms from the Cu(111) surface occurs at 377 K. The formation of an extended two‐dimensional (2D) network is observed with scanning tunneling microscopy (STM). A honeycomb‐like lattice of metalated pyrphyrin molecules is formed by intermolecular connection via the two cyano groups at the periphery of pyrphyrin as well as Cu adatoms. Dehydrogenation at the periphery of the molecule is observed during annealing at 520 K. The surface‐adsorbed metal‐pyrphyrin has the potential to serve as a molecular catalyst. Abstract :